Different strategies of altering the cell wall to study the impact that these introduced changes have on plant resistance to pathogens - DeTemple, Megan F.; Zabotina, Olga A. (Frontiers in Plant Science, 2025)
The cell wall (CW) plays many vital roles in plant fitness, ranging from plant development to defense against pathogens. There are many strategies used to make modifications to the CW and observe the consequences it has on plant development, physiology, and resistance to biotic and abiotic stresses. The most common methods used to change the CW include altering CW synthesizing gene expression by producing gene knockouts or overexpression lines, treating with CW enzyme inhibitors, applying exogenous hydrolases, and expressing CW degrading enzymes (CWDEs) in the plant. Alterations in the CW can change plant responses to pathogens through a variety of mechanisms including inducing plant immune pathways, eliciting a variety of PTI responses or by making the CW more resistant to pathogen infection. This review will highlight the insights gained about CW-mediated resistance and the function of each type of polysaccharide in pathogenesis grouped by each CW-modifying technique. Finally, the different advantages and disadvantages of these approaches will be discussed.